MOSSBAUER STUDY OF YTTRIUM IRON GARNET EPITAXIAL FILMS MAGNETIC MICROSTRUCTURE - V.O. Kotsyubynsky; V.V. Moklyak; B.K. Ostafiychuk (Vasyl Stefanyk Precarpathian National University, 2014)
The magnetic microstructure of the yttrium iron garnet epitaxial films surface layer were studied by conversion electronic Mossbauer  spectroscopy method. The presence of two magnetically non-equvivalent positions of Fe3+ ions in tetrahedral sites of garnet structure and a paramagnetic phase  formed by Fe2+ ions were fixed. Using the  model  of  mixed  magnetic  and  quadrupole  interaction  by  the diagonalization of the nuclear Hamiltonian matrix the information about the spatial orientation of the cation sublattices magnetic moments  was obtained and the components of electric field gradient tensor at 57Fe nuclei in different crystal non-equvivalent  positions were calculated